Frailty: Past, present, and future? - Dongmin Kwak; LaDora V. Thompson (Sports Medicine and Health Science, 2021)
The prevalence of frailty across the world in older adults is increasing dramatically and having frailty places a person at increased risk for many adverse health outcomes, including impaired mobility, falls, hospitalizations, and mortality. Globally, the concept of frailty is gaining attention and the scientific field has made great strides in identifying and conceptually defining frailty through consensus conferences, in advancing the overall science of frailty by drawing on basic science discoveries including concepts surrounding the hallmarks of aging, resilience, and intrinsic capacities, and in identifying the many challenges faced by professionals within diverse clinical settings. Currently, it is thought that frailty is preventable, thus the identification of a person's degree of frailty is vital. Identification of frailty is achievable through widely used frailty screening tools, which are valid, reliable, and easy to use. Following the identification of a person's degree of frailty, targeted intervention strategies, such as physical activity programs must be implemented. In this perspective, we provide a historical perspective of the frailty field since the last quarter of the 20th century to present. We identify the proposed underlying pathophysiology of multiple physiological systems, including compromised homeostasis and resilience. Next, we outline the available screening tools for frailty with a physical performance assessment and highlight specific benefits of physical activity. Lastly, we discuss current scientific evidence supporting the physical activity recommendations for the aging population and for older adults with frailty. The goal is to emphasize early detection of frailty and stress the value of physical activity.